2005
DOI: 10.1111/j.1365-2516.2005.01121.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of factor VIII gene mutations in 101 patients with haemophilia A: mutation analysis by inversion screening and multiplex PCR and CSGE and molecular modelling of 10 novel missense substitutions

Abstract: Haemophilia A (HA) is an X-linked bleeding disorder caused by diverse mutations in the human coagulation factor VIII (FVIII) gene. We have analysed DNA from 109 unrelated Indian patients with HA for their FVIII gene defects. Among these patients 89 (82%) had severe (FVIII:C <1%) HA, 11 (10%) had moderate (FVIII:C 1-5%) HA and nine (8%) had mild (FVIII:C 5-30%) HA. These patients were first screened for the common intron 22 and intron 1 inversions. Inversion negative samples were screened for point mutations by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
63
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 32 publications
10
63
0
Order By: Relevance
“…Our study confirms the well-known correlation between the type of mutation and the severity of HA. The type of mutations found was in agreement with results reported in other settings (Oldenburg and Pavlova 2006;Fernández-LĂłpez et al 2005;Jayandharan et al 2005;Deszo et al 2006). As would be expected, most severe HA patients carry a molecular defect leading to a null allele (large deletion, inversion, nonsense, and insertion/deletion mutations), whereas missense mutations have been found in the majority of moderate (68%) and mild HA patients (81%).…”
Section: Discussionsupporting
confidence: 82%
“…Our study confirms the well-known correlation between the type of mutation and the severity of HA. The type of mutations found was in agreement with results reported in other settings (Oldenburg and Pavlova 2006;Fernández-LĂłpez et al 2005;Jayandharan et al 2005;Deszo et al 2006). As would be expected, most severe HA patients carry a molecular defect leading to a null allele (large deletion, inversion, nonsense, and insertion/deletion mutations), whereas missense mutations have been found in the majority of moderate (68%) and mild HA patients (81%).…”
Section: Discussionsupporting
confidence: 82%
“…The types of mutations found were in agreement with results reported in other settings (Table 2). [15][16][17][18][19][20][21][22][23][24] As expected, most of patients with severe HA carry a molecular defect predicting a null allele (large deletion, inversion, nonsense, and insertion/deletion mutations), whereas missense mutations have been found in the majority of patients with moderate (68%) and mild HA (80%).…”
Section: Discussionmentioning
confidence: 99%
“…For example, codon with three different amino acid changes are the arginine codon 531in exon 11 , codon 1781 in exon 16 (Faridi et al, 2011) and codon 2150 in exon 23 (Liu et al, 2002;Cutler et al, 2002;Habart et al, 2002;Fernandez-Lopez et al, 2005), which has been reported 61 times (Table 1), since arginine is involved in 25% of all missense mutations found so far and play a crucial role in protein function. Ahmed et al (2005) carried out mutation studies in inversion negative hemophilia A patients by the high performance liquid chromatography (dHPLC) method and found 11 missense mutations, and some other mutations (Ahmed et al, 2005), whereas Jayandharan et al (2005) detected 101 mutations by using multiplex polymerase chain reactions (PCRs) and the Cap analysis gene expression (CAGE) technique, of which 21 were missense mutations (Jayandharan., 2005). There is a report of missense mutation being pre-dominantly found in the A1 and A2 domains (Bogdanova et al, 2005).…”
Section: Missense and Nonsense Mutationsmentioning
confidence: 99%